GENRE EVOLUTION OF THE PSALM AND ECCLESIASTICAL MINIATURE - VARAKUTA, Maryna (Studia Universitatis Babes-Bolyai Musica, 2022)
The article deals with the evolutionary processes of development of psalm and ecclesiastical miniature genres in choral music from the Renaissance to the present. It has been found that the wide possibilities of creating liturgical and non-church, concert and stage spiritual works gave the way to the enrichment of canonical канонічних principles of such traditional genre models as psalm and ecclesiastical miniature with individual stylistic features. Accordingly, gaining more and more popularity in church and secular music practice, psalms and ecclesiastical (prayer) miniatures have acquired nmiew qualities – canonical flexibility, genre mobility, openness to style and stylistic syntheses and authorial individualization in both textual and much more in musical aspects. The research methodology is based on historical-typological, genre-stylistic, and analytical methods. The historical-typological method relates to the problems of historical evolution of psalm and ecclesiastical miniature genre models, genre-stylistic and analytical methods allow to come to reasonable conclusions about the peculiarities of prayer texts in choral compositions created by modern Ukrainian composers. Traditions of Ukrainian spiritual music and at the same time the modern tendencies of the musical language are brightly shown in choral compositions. It is noted that the level of correlation between traditional and innovative referrence to psalm and ecclesiastical miniature genre models is determined by the individual creative approach of a certain composer, which requires making references to ecclesiastical texts and creating unique motets on their basis.